Effect of Silica on Rice Agromorphological Diversity Under Iron Toxicity Conditions in Lowland Rice of Guinea Conakry - Barry, Mamadou Laho; Sawadogo, Nerbewende; Ouedraogo, Mahamadi Hamed; Nanema, Kiswendsida Romaric; Barry, Mamadou Billo; Bationo-Kando, Pauline; Sawadogo, Mahamadou (European Scientific Journal, ESJ, 2019)
Rice is the second most important cereal in West Africa and is an essential element in the diet of the population. However, iron toxicity is one of the major edaphic constraints in lowland rice cultivation. The large amount of ferrous ions in solution causes an imbalance in nutrients involving a nutritional disorder affecting the growth of crops including rice. The present study conducted in 2014 in Guinea Conakry in the lowlands of the Kilissi Agronomic Research Station aimed to evaluate the effect of silica on reducing of the effect of iron toxicity in rice. Thus, rice varieties were evaluated according to a split plot device with three (3) randomized replications for two factors (rice varieties and silica doses) and three (3) silica treatments (D0 g, D120 g and D240 g). The results showed a significant effect of silica on most agronomic parameters of the rice varieties tested. The D240 g dose gave the best yields of up to 6.9 t/h. Seventeen (17) varieties exhibited good agronomic characteristics of yield, cycle, and weight of 1000 grains. In addition, the study reveals a possibility of reducing the effect of iron toxicity in lowlands in Guinea by the combined use of silica and rice varieties resistant or tolerant to iron. The genetic variability observed with certain tolerant varieties with ferrous toxicity like CK4 could be exploited in our national rice breeding program.